3D-Printed Testing Plate for the Optimization of High C-Rates Cycling Performance of Lithium-Ion Cells. Issue 5 (3rd May 2021) - Carbonari, Gilberto; Scurtu, Rares-George; Waldmann, Thomas; Radloff, Sonja; Flügel, Marius; Hoffmann, Alice; Wohlfahrt-Mehrens, Margret
Abstract : Nowadays, long charging times have become one of the main limitations to a greater worldwide spread of electric vehicles (EV). Enabling high C-rates charging is a promising approach to eliminate this problem and alleviate range anxiety. When a battery is charged at high currents, several factors have to be taken into account. Temperature is certainly a key parameter because when it is too high this can lead to degradation of components (binder, electrolyte, active material, etc), however, when it is too low intercalation kinetics becomes sluggish. Using 3D-printed testing plates (PP3D plates) with Li-reference electrode, we developed a tool for electrochemical investigations of pouch cells. These plates enabled to build a new well-designed 3-electrode pouch cell. This setup allows the identification of the best high C-rate cycling procedure to improve the performance and cycling life of the lithium ion cells. We explored the electrochemical behavior of NMC811 cathodes and graphite anodes, during high discharge C-rates test up to 7 C and charge C-rates up to 2 C. Moreover, the temperature influence on charging performance and longtime cycling stability is investigated. The cells cycled at 25 °C using optimized procedures reached an 80% state of health after more than 1000 cycles.